ACTIVE PEDAGOGY OR ACTIVE METHODS? THE CASE OF ACTIVE LEARNING AT UNIVERSITY - Espejo Leupin, Roberto Mauricio (2016)
In this paper we discuss the active learning approach that has been spread in university classrooms in relation to its pedagogical predecessors, particularly the New European School movement and the American Progressive Education. This relationship allows us to understand the array of teaching-learning methods used today at university under a historical perspective, including differences with its predecessors. Particularly, we will discuss the difference between active methods and the more general concept of active pedagogy, which implies an educational philosophy more radically centered on the students. This enables us to outline possible evolution lines in the practice of active pedagogy at university.